Telecommunications is an Essential Service - Gregory, Mark A (Journal of Telecommunications and the Digital Economy, 2017)
The Australian Government has responded to the Productivity Commission inquiry into the Universal Service Obligation (USO). The primary issues identified by the Government include the cost of providing the USO and how it’s provision might be competitively distributed. Secondary issues and issues that did not get a guernsey include improved access to telecommunications (and broadband) for the socially disadvantaged, improved service reliability and quality and an acknowledgement that telecommunications is an essential service. Over the next decade telecommunications will take centre stage as the way that we live, interact with our family and friends and the things around us changes faster than at any time in history. Papers in this issue of the Journal cover a range of topics that cover historical events, book reviews and international telecommunications markets including a unique look at the development of the telecommunications market in Canada.